An ecosystem services approach to choosing environmental indicators for state of environment reports - Dymond, John; Ausseil, Anne-Gaëlle (New Zealand Science Review, 2019)
State of environment (SOE) reports aim to give people a summa-ry of the environment through indicators. When an SOE report is associated with specific environmental goals, it is straightforward to develop indicators from the goals. However, it is difficult when there are no specific goals. We explore the use of an ecosystem services framework to develop a general set of indicators for the land/water environment by considering a full range of benefits humans gain from the environment. This analysis shows that the national SOE report, Environment Aotearoa, is missing many indicators required for a broader picture. Many of the missing impact indicators relate to human health and are highly relevant. Our sparse networks of data collection reflect the low population of New Zealand and the limited resources that can be reasonably applied to data collection. An encouraging area of improvement is the use of more targeted indicators developed from the ground up in collaboration with stakeholders. While the analysis presented here is focussed on New Zealand, other countries are also data-sparse and face similar issues, and would benefit from a gap analysis of environmental indicators based on ecosystem services.